2014
DOI: 10.1097/qad.0000000000000447
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, incidence and predictors of peripheral neuropathy in African adults with HIV infection within the DART trial

Abstract: Objectives: We investigated the prevalence, incidence and predictors of new peripheral neuropathy episodes in previously untreated, symptomatic HIV-infected Ugandan/Zimbabwean adults initiating zidovudine-based antiretroviral therapy (ART).Design: An open-label, multicentre, randomized trial. Methods:Peripheral neuropathy was self-reported at 12-weekly clinic visits. Cox regression models (excluding participants reporting preexisting peripheral neuropathy at ART initiation), considered sex; pre-ART WHO stage, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 37 publications
3
8
0
Order By: Relevance
“…Age as a risk factor for PN, however, was reported many times before and proved to be so in HIV patients above 34 years of our cohort as well (Evans et al 2011; Wadley et al 2011; Nwabueze et al 2012; Chen et al 2013; Kiwuwa-Muyingo et al 2014; Tumusiime et al 2014a, b). As possible explanation, on the one hand, aging increases vulnerability towards neuronal toxicity, on the other hand is the HIV population’s median age rapidly increasing due to continuously improved management of infected persons in Sub-Sahara Africa, and so is the prevalence of PN.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…Age as a risk factor for PN, however, was reported many times before and proved to be so in HIV patients above 34 years of our cohort as well (Evans et al 2011; Wadley et al 2011; Nwabueze et al 2012; Chen et al 2013; Kiwuwa-Muyingo et al 2014; Tumusiime et al 2014a, b). As possible explanation, on the one hand, aging increases vulnerability towards neuronal toxicity, on the other hand is the HIV population’s median age rapidly increasing due to continuously improved management of infected persons in Sub-Sahara Africa, and so is the prevalence of PN.…”
Section: Discussionsupporting
confidence: 51%
“…This number somewhat ranges within the ratios found in other studies performed in sub-Sahara Africa. Such studies reported prevalence of 6% and 57% in South Africa, respectively (Boulle et al 2007; Wadley et al 2011), 13% in Malawi (Beadles et al 2009), 20.7% and 36% in Kenya, respectively (Hawkins et al 2007; Mehta et al 2010), 36% in Uganda (Forna et al 2007), 24% in Uganda/Zimbabwe (Kiwuwa-Muyingo et al 2014), 59% in Rwanda (Tumusiime et al 2014a), and 28% in Cameroon (Luma et al 2012). A recent study by Benevides et al 2017 in southern Brazil unveiled 31.3% of PN prevalence in PLHIV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Peripheral sensory polyneuropathy was the most common ART adverse effect in this study. Older age has been shown to be associated with peripheral neuropathy in both HIV infected and uninfected people [ 37 , 38 ]. Zidovudine and tenofovir disoproxil fumarate are still in use in LMIC and clinicians should continue to monitor elderly patients for adverse effects while on these medicines.…”
Section: Discussionmentioning
confidence: 99%
“…Retention in care of 71.4% after a median follow up time of 5.6 years (IQR: 2.4-9.9) was comparable with that of a younger population (74.4%) at 36 months with a median age of 35 years (IQR: [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] in the Zimbabwe National ART Program and higher than that observed in a Kenyan cohort study (54%) at 36 months [33,34]. However, unlike with this larger…”
Section: Plos Onementioning
confidence: 90%